That's a Stretch: Reconstructing, Rearticulating, and Commodifying Yoga - Antony, Mary Grace (Frontiers in Communication, 2018)
Yoga’s immense popularity prompts concerns about the extent to which cultural appropriation has compromised its original philosophy. This study examines how yoga is constructed by mainstream news media discourse, with an emphasis on its religious versus spiritual attributes. In doing so, I consider yoga as a commodity articulated through globalization, capitalism, and transculturation, the product of cultural appropriation (Rogers, 2006) and symbolic displacement (Wilson, 2012). Findings demonstrate that yoga’s discursive detachment from religious origins facilitates its rearticulation as: a means to achieve physical, emotional, and mental wellbeing; a flexible experience amenable to other faiths and creeds; and an elite and exotic commodity embedded within overlapping consumerist structures of capitalism and spiritual renewal. These findings reflect the extent to which its global appropriation complicates conceptualizations of cultural ownership and the authenticity of indigenous artifacts.